Stranded Assets and Thermal Coal: An analysis of environment-related risk exposure - Caldecott, B; Kruitwagen, L; Dericks, G; Tulloch, D; Kok, I; Mitchell, J (Smith School of Enterprise and the Environment, 2016)
The principal aim of this report is to turn the latest research on environment-related risk factors facing thermal coal assets into actionableinvestment hypotheses for investors. By examining the fundamental drivers of environment-related risk, creating appropriate measures to differentiate the exposure of different assets to these risks, and linking this analysis to company ownership, debt issuance, and capital expenditure plans, our research can help to inform specific investor actions related to risk management, screening, voting, engagement, and disinvestment. To our knowledge, this report contains the most comprehensive and up-todate analysis of the environment-related risks facing thermal coal companies that is publicly available.